How the Loyalty of Expedition Business Can Be Formed Through Trust and Satisfaction - Esti Nur Wakhidah; Budhi Haryanto (Sebelas Maret Business Review, 2017)
The purpose of this study is to examine the role of satisfaction and trust in mediating the relationship between service quality and brand image, and customer's intention to be loyal. The data is collected using survey and conducted by distributing questionnaire through a website. Website is selected as a media to distribute th research instrument because today marketplace shows a shift from offline to online platform. This study selected 200 people who have the intention to loyal with Jalur Nugraha Ekakurir (JNE) service as samples. Structural Equation Model (SEM) is statistical method chosen to elaborate the relationship among the variables. The result of this research indicates that service quality and brand image have positive and significant effect on satisfaction and trust. In addition, this research also find the mediation effect of satisfaction and trust in shaping customer loyalty. This study also discusses the implications from theoretical, practical, and future research, point of view. Keywords: Service Quality, Brand Image, Customer Satisfaction, Customer Trust, Customer Loyalty